Vibration harvesting integrated into vehicle suspension and bodywork - Souad Touairi; Mustapha Mabrouki (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This work proposes a new piezoelectric transducer system with four freedoms of movement modelled and evaluated by mechatronic techniques. The proposed modelling techniques (finite element and bond graph) were performed in a 20-Sim framework attached to the ANSYS software. The established harvester system has the ability to increase the driver's comfort when travelling on several types of road surfaces. The piezoelectric harvester is designed to investigate and provide the health requirement and ride comfort of the vehicle's drives on random road surfaces. The simulation results affirm that the improved piezoelectric transducer arrangement is more productive for various aspects. The power recovery is significantly enhanced as well as the driving comfort on the three road categories. Finally, the harvestable power amount is highlighted and is graphically discussed for several specific applications.